2019
DOI: 10.1101/591412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Area-specific mapping of binocular disparity across mouse visual cortex

Abstract: Binocular disparity, the difference between left and right eye images, is a powerful cue for depth perception. Many neurons in the visual cortex of higher mammals are sensitive to binocular disparity, with distinct disparity tuning properties across primary and higher visual areas. Mouse primary visual cortex (V1) has been shown to contain disparity-tuned neurons, but it is unknown how these signals are processed beyond V1. We find that disparity signals are prominent in higher areas of mouse visual cortex. Pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 36 publications
4
48
0
Order By: Relevance
“…Mice can discriminate stereoscopic depth (Samonds et al, 2019) and disparity-sensitive neurons similar to those characterized in other mammals have been found in V1 (Scholl et al, 2013) and in higher-order areas LM and RL (La Chioma et al, 2019). Clear differences in neurons' preferred disparities were observed across these areas, with area RL being specialized for disparities corresponding to nearby visual stimuli (La Chioma et al, 2019).…”
Section: Introductionsupporting
confidence: 56%
“…Mice can discriminate stereoscopic depth (Samonds et al, 2019) and disparity-sensitive neurons similar to those characterized in other mammals have been found in V1 (Scholl et al, 2013) and in higher-order areas LM and RL (La Chioma et al, 2019). Clear differences in neurons' preferred disparities were observed across these areas, with area RL being specialized for disparities corresponding to nearby visual stimuli (La Chioma et al, 2019).…”
Section: Introductionsupporting
confidence: 56%
“…Even in the absence of horizontal head and eye movements and the asymmetry noted above, changes in the position of the two eyes as a consequence of head tilt could potentially perturb ocular alignment critical for binocular depth perception (Wallace et al, 2013). Despite this, there is evidence for neural representations of binocular disparities in mouse visual cortex (Scholl et al, 2013, La Chioma et al, 2019. Future experiments could investigate the link between the neural representations of binocular disparity, binocular gaze and visual behaviors in freely moving mice.…”
Section: Asymmetry In Horizontal Gaze Movements Between the Two Eyesmentioning
confidence: 99%
“…Recent electrophysiological recordings in the rat point to an even finer graded somatotopy representing the whisker rows in RL (Mohan et al, 2019). Interestingly, another recent study revealed that RL, which is typically considered a higher order visual area, is specialized for encoding visual stimuli very close to the mouse, within reach of the whiskers, suggesting the existence of a visuotactile map of near space in RL (La Chioma et al, 2019). While these insights provide some clarification of the gross functional organization of rodent PPC, further work is needed to disentangle the partially overlapping and intermingled connections with visual, auditory, and somatosensory areas that likely form the basis of the multi-sensory integrative power of PPC.…”
Section: Functional Organization Of Ppc With Respect To Sensory Modalmentioning
confidence: 99%